2008
DOI: 10.1159/000187643
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Collagen by Metalloproteinase 2 in Patients with Abdominal Hernias

Abstract: Background: The groin hernia is a significant social and economic problem of our times. The pathogenesis of the disease is not clear. The metalloproteinases (MMP) are the group of proteolytic enzymes responsible for the degradation of extracellular matrix proteins and the basic membrane of blood vessels. The aims of our study were: (1) to estimate the MMP-2 levels in the blood and tissues of patients with a groin hernia; (2) to answer the question of whether changes in MMP-2 activity correlate with the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…Significantly higher MMP-2 levels have been found in patients with a direct inguinal hernia than in those with an indirect inguinal hernia and controls. These results were derived from larger studies on both fascia transversalis and serum, suggesting that the MMP-2 level was also increased systemically in these patients 32,65,67 . These conclusions were based on protein level measurements and not MMP-2 proteolytic activity in the fascia transversalis.…”
Section: Matrix Metalloproteinase-mediated Collagen Breakdownmentioning
confidence: 73%
See 4 more Smart Citations
“…Significantly higher MMP-2 levels have been found in patients with a direct inguinal hernia than in those with an indirect inguinal hernia and controls. These results were derived from larger studies on both fascia transversalis and serum, suggesting that the MMP-2 level was also increased systemically in these patients 32,65,67 . These conclusions were based on protein level measurements and not MMP-2 proteolytic activity in the fascia transversalis.…”
Section: Matrix Metalloproteinase-mediated Collagen Breakdownmentioning
confidence: 73%
“…Another study on skin fibroblasts from patients with a recurrent inguinal hernia showed a significant increase in type III procollagen mRNA, and a concomitant increase in MMP-1 and MMP-13 levels, compared with controls 55 . A significant increase in serum MMP-2 was also found in patients with a recurrent inguinal hernia compared with controls 67 . One caveat is that only a fraction of the total circulating MMP-2 was measured.…”
Section: Studies On Collagen Metabolism In Recurrent Inguinal Herniamentioning
confidence: 76%
See 3 more Smart Citations